A collection of novel Lotus japonicus LORE1 mutants perturbed in the nodulation program induced by the Agrobacterium pusense strain IRBG74 - García-Soto, Ivette; Andersen, Stig U.; Monroy-Morales, Elizabeth; Robledo-Gamboa, Mariana; Guadarrama, Jesús; Aviles-Baltazar, Norma Yaniri; Serrano, Mario; Stougaard, Jens; Montiel, Jesús (Frontiers in Plant Science, 2024)
The Lotus japonicus population carrying new Lotus retrotransposon 1 (LORE1) insertions represents a valuable biological resource for genetic research. New insertions were generated by activation of the endogenous retroelement LORE1a in the germline of the G329-3 plant line and arranged in a 2-D system for reverse genetics. LORE1 mutants identified in this collection contributes substantially to characterize candidate genes involved in symbiotic association of L. japonicus with its cognate symbiont, the nitrogen-fixing bacteria Mesorhizobium loti that infects root nodules intracellularly. In this study we aimed to identify novel players in the poorly explored intercellular infection induced by Agrobacterium pusense IRBG74 sp. For this purpose, a forward screen of > 200,000 LORE1 seedlings, obtained from bulk propagation of G329-3 plants, inoculated with IRBG74 was performed. Plants with perturbed nodulation were scored and the offspring were further tested on plates to confirm the symbiotic phenotype. A total of 110 Lotus mutants with impaired nodulation after inoculation with IRBG74 were obtained. A comparative analysis of nodulation kinetics in a subset of 20 mutants showed that most of the lines were predominantly affected in nodulation by IRBG74. Interestingly, additional defects in the main root growth were observed in some mutant lines. Sequencing of LORE1 flanking regions in 47 mutants revealed that 92 Lotus genes were disrupted by novel LORE1 insertions in these lines. In the IM-S34 mutant, one of the insertions was located in the 5´UTR of the LotjaGi5g1v0179800 gene, which encodes the AUTOPHAGY9 protein. Additional mutant alleles, named atg9-2 and atg9-3, were obtained in the reverse genetic collection. Nodule formation was significantly reduced in these mutant alleles after M. loti and IRBG74 inoculation, confirming the effectiveness of the mutant screening. This study describes an effective forward genetic approach to obtain novel mutants in Lotus with a phenotype of interest and to identify the causative gene(s).